BS ISO 22028-3. Photography and graphic technology. Extended colour encodings for digital image storage, manipulation and interchange. Part 3. Reference input medium metric RGB colour image encoding (RIMM RGB) (9th May 2022) - British Standards Institution,
No abstract available